Corticotropin-releasing factor-like diuretic hormone acts as a gonad-inhibiting hormone in adult female, Rhodnius prolixus - Al-Dailami, Areej N.; Orchard, Ian; Lange, Angela B. (Frontiers in Endocrinology, 2023)
Within insects, corticotropin-releasing factor / diuretic hormones (CRF/DHs) are responsible for the modulation of a range of physiological and behavioural processes such as feeding, diuresis, and reproduction. Rhopr-CRF/DH plays a key role in feeding and diuresis in Rhodnius prolixus, a bloodgorging insect and a vector for human Chagas disease. Here, we extend our understanding on the role of this neurohormone in reproduction in adult female R. prolixus. Double-label immunohistochemistry displays co-localized staining of CRF-like and the glycoprotein hormone (GPA2/GPB5) subunit GPB5like immunoreactivity in the same neurosecretory cells (NSCs) in the mesothoracic ganglionic mass (MTGM) and in their neurohemal sites in adult female R. prolixus, suggesting these peptides could work together to regulate physiological processes. qPCR analysis reveals that the transcript for Rhopr-CRF/DH receptor 2 (Rhopr-CRF/DH-R2) is expressed in reproductive tissues and fat body (FB) in adult female R. prolixus, and its expression increases post blood meal (PBM), a stimulus that triggers diuresis and reproduction. Using RNA interference, transcript expression of Rhopr-CRF/DH-R2 was knocked down, and egg production monitored by examining the major yolk protein, vitellogenin (Vg), the number and quality of eggs laid, and their hatching ratio. Injection of dsCRFR2 into adult females reduces Rhopr-CRF/DH-R2 transcript expression, accelerates oogenesis, increases the number of eggs produced, and reduces hatching rate in female R. prolixus. Downregulation of Rhopr-CRF/DH-R2 leads to an increase in the transcript expression of RhoprVg1 in the fat body and ovaries, and increases the transcript level for the Vg receptor, RhoprVgR, in the ovaries. A significant increase in Vg content in the fat body and in the hemolymph is also observed. Incubation of isolated tissues with Rhopr-CRF/DH leads to a significant decrease in transcript expression of RhoprVg1 in the fat body and RhoprVg1 in the ovaries. In addition, Rhopr-CRF/DH reduces transcript expression of the ecdysteroid biosynthetic enzymes and reduces ecdysteroid titer in the culture medium containing isolated ovaries. These results suggest the involvement of the CRF-signaling pathway in reproduction, and that Rhopr-CRF/DH acts as a gonad-inhibiting hormone in the adult female R. prolixus, as previously shown for the colocalized glycoprotein, GPA2/GPB5.